Islamic conceptualisation of knowledge management - Yaakub, Muhamadul Bakir (2010)
This paper is an attempt to address “The Fundamental Theory of Knowledge Management” from Islamic point of views, to draw the notion of “Islamic Worldview” of knowledge, especially in terms of understanding its nature in the reality of knowledge society.Thus, with the assumption that once knowledge is managed, then it is possible to look at its behaviours, functions, and process of development in the form of scientific realm.Hypothetically, if there were no single theory formulated to identify the nature of knowledge, then how can it be managed and achieve its goals?